Throughput evaluation of a satellite-switched CDMA (SS - Gerakoulis, D.P.
This paper presents throughput evaluation of a satellite-switched code-division multiple-access (SS/CDMA) system which operates under demand assignment control. SS/CDMA provides both multiple access and switching to a geostationary multibeam satellite. Multiple access is resolved by space, frequency, and code division. Space division is introduced by the multibeam antennas that provide frequency reuse in each beam. The spectrum is then channelized into frequency bands where each band is accessed by code division for both the uplink and downlink. The satellite on-board performs the switching function, which is also based on compatible code-multiplexed switching. The switch may route both circuit calls and data packets which are assigned upon request. The on-board code-division switch operates under the control of a channel assignment algorithm. We provide channel assignment algorithms for optimum, suboptimum, and random switch operation. The system throughput has been evaluated for each case and compared. Performance analysis has been carried out for the case of the optimum switch scheduling. The analysis is based on a discrete-time Markovian model, and provides the call-blocking probabilities and data packet delays. Computer simulations have been used to evaluate the performance of the optimum, suboptimum, and random cases. It is shown that the circuit call-blocking probabilities achieved for these cases are almost the same. The optimum algorithm achieves the minimum data packet delay, while the performance of the suboptimum algorithm is slightly better than the random one. Furthermore, data packets may be routed via the switch with limited delays, even with a heavy load of circuit calls
Keywords: SS/CDMA demand assignment system; Call-blocking probabilities; Channel assignment algorithm; Circuit calls routing; Code-division multiple-access.; Code-division switch; Code-multiplexed switching; Computer simulations; Data packet delays; Data packets routing; Demand assignment control; Discrete-time Markovian model; Downlink; Frequency bands; Frequency division; Frequency reuse; Geostationary multibeam satellite; Multibeam antennas; Optimum switch operation; Optimum switch scheduling; Performance analysis; Random switch operation; Satellite on-board switch; Satellite-switched CDMA; Space division; Suboptimum switch operation; Throughput; Uplink